The Canadian Federation of Earth Sciences Scientific Statement on Climate Change – Its Impacts in Canada, and the Critical Role of Earth Scientists in Mitigation and Adaptation - Burn, Christopher R.; Cooper, Mark; Morison, Stephen R.; Pronk, Toon; Calder, John H. (Geoscience Canada, 2021)
The Canadian Federation of Earth Sciences (CFES) has issued this statement to summarize the science, effects, and implications of climate change. We highlight the role of Earth scientists in documenting and mitigating climate change, and in managing and adapting to its consequences in Canada. CFES is the coordinated voice of Canada’s Earth Sciences community with 14 member organizations representing some 15,000 geoscientists. Our members are drawn from academia, industry, education, and government. The mission of CFES is to ensure decision makers and the public understand the contributions of Earth Science to Canadian society and the economy.Climate change has become a national and global priority for all levels of government. The geological record shows us that the global climate has changed throughout Earth’s history, but the current rates of change are almost unprecedented. Over the last 70 years, levels of common greenhouse gases (GHGs) in the atmosphere have steadily increased. Carbon dioxide (CO2) concentration is now 418 parts per million — its highest of the last three million years. The chemical (isotopic) composition of carbon in the atmosphere indicates the increase in GHGs is due to burning fossil fuels. GHGs absorb energy emitted from Earth’s surface and re-radiate it back, warming the lower levels of the atmosphere. Climatic adjustments that have recently occurred are, in practical terms, irreversible, but further change can be mitigated by lowering emissions of GHGs.Climate change is amplified by three important Earth system processes and effects. First, as the climate warms evaporation increases, raising atmospheric concentrations of water vapour, itself a GHG — and adding to warming. Second, loss of ice cover from the polar ice sheets and glaciers exposes larger areas of land and open water — leading to greater absorption of heat from the sun. Third, thawing of near-surface permafrost releases additional GHGs (primarily CO2 and methane) during decay of organic matter previously preserved frozen in the ground. Some impacts of climate change are incremental and steadily occurring, such as melting of glaciers and ice sheets, with consequent sea level rise. Others are intermittent, such as extreme weather events, like hurricanes — but are becoming more frequent. Summer water shortages are increasingly common in western Canada as mountain snowpacks melt earlier and summer river flows decline. In northern Canada, warming and thawing of near-surface permafrost has led to deterioration of infrastructure and increased costs for buildings that now require chilled foundations. Other consequences of unchecked climate change include increased coastal erosion, increases in the number and size of wildfires, and reduction in winter road access to isolated northern communities. Reductions in net GHG emissions are urgently required to mitigate the many effects of further climate change. Industrial and public works development projects must now assess the effects of climate change in their planning, design, and management. Cities, municipalities, and rural communities need to plan new residential development carefully to avoid enhanced risk of flooding, coastal erosion, or wildfire.Earth Science knowledge and expertise is integral to exploration and development of new metals and Earth materials required for a carbon-neutral future, and in the capture and storage of CO2 within the Earth. Earth Science is also central to society’s adaptation to new climatic regimes and reduction of risks. This includes anticipation, assessment, and management of extreme events, development of new standards and guidelines for geotechnical and engineering practice, and revision to regulations that consider climate change. Geoscientists also have an important role in the education of students and the public on the reasons for necessary action. Canada is uniquely positioned with its strong global geoscientific leadership, its vast landmass, and its northern terrain to effectively leverage research activities around climate change. Geoscience tools and geoscientists’ skills will be integral to Canada’s preparation for climate change.